Ambiguous Policy Announcements - Michelacci, Claudio; Paciello, Luigi (Review of Economic Studies, 2020)
Abstract We study the effects of monetary announcements when agents face Knightian uncertainty about the commitment capacity of the monetary authority. Households are ambiguity averse and differentially exposed to inflation due to differences in wealth. In response to the announcement of a future monetary loosening, only wealthy households (creditors) act as if the announcement will be fully implemented, due to the potential wealth losses from future inflation. As a result the economy responds as if aggregate net wealth falls, which attenuates the effects of the announcement. Redistributing from super-wealthy to middle-wealthy households makes the announcement more expansionary, in the extreme as expansionary as under a fully credible announcement.